Unveiling the potential of a protease inhibitor from Pleiogynium cerasiferum to combat Helicoverpa armigera by employing sequential purification and multivariate statistical analysis - Vijay Kumar Shukla; Prabhash Kumar Pandey; Santanu Mallik; Ashutosh Shrivastava; Amita Jain; Sangram Singh; Farrukh Jamal (Discover Agriculture, 2024)
Abstract Crop protection is heavily dependent on the use of chemical pesticides that are not only toxic but also detrimental to the environment. To minimize the chemical approaches of crop protection, this study investigates a natural protease inhibitor PCPI (Pleiogynium cerasiferum protease inhibitor) extracted from the seeds of Pleiogynium cerasiferum as a viable bioresource with biopesticidal properties. PCPI demonstrated inhibitory activity of 92% against bovine trypsin and 89% against Helicoverpa armigera's midgut proteolytic enzymes. Characterization of PCPI revealed a 24 kDa protein with critical inhibitory concentrations of 1.53 µg/ml for H. armigera midgut proteases and 1.31 µg/ml for bovine trypsin. At the concentration of 0.5% (w/w) of PCPI, the deformities in pupae were ~ 82%, adult insects ~ 87%, and egg-laying as well as egg hatching capacity dropped by ~ 81% and 17% respectively. Principal component analysis (PCA), complemented by hierarchical clustering, was applied to assess the nuanced effects of PCPI across the pest's lifecycle. The analysis identified deformities in pupae, adult, adult emergence, and notably, egg laying reduction as variables most responsive to PCPI concentrations. Hierarchical clustering analysis corroborated these PCA findings indicating a concentrated influence on developmental stages and reproduction metrics, signifying the multifaceted impact of PCPI. These insights affirm PCPI's promise as a cornerstone of eco-friendly pest management strategies.